2002
DOI: 10.1080/01652176.2002.9695126
|View full text |Cite
|
Sign up to set email alerts
|

Equine herpesvirus 1 and 4 infections: An update

Abstract: Summary Equine herpesvirus 1 (EHV1) and equine herpesvirus 4 (EHV4) are important ubiquitous equine pathogens, causing much damage to the viral horse industry. EHV1 strains are associated with respiratory disease, abortion, and paresis/paralysis, whereas EHV4 strains are predominantly associated with respiratory disease. In the past decades much research effort has been put into improving knowledge about these viruses. In this paper the current state of knowledge of these viruses and the most important asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 135 publications
2
64
0
2
Order By: Relevance
“…Equine herpesvirus type 1 (EHV-1) is an Alphaherpesvirus of the genus Varicellovirus and predominates in the horse population as a respiratory pathogen, occasionally causing abortions and neurological disease [6,7]. The EHV-1 modified-live virus vaccine strain RacH is commonly used to vaccinate horses against EHV-1 in Europe and in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Equine herpesvirus type 1 (EHV-1) is an Alphaherpesvirus of the genus Varicellovirus and predominates in the horse population as a respiratory pathogen, occasionally causing abortions and neurological disease [6,7]. The EHV-1 modified-live virus vaccine strain RacH is commonly used to vaccinate horses against EHV-1 in Europe and in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Allen et al [3] reported a sudden increase of the 1B type in the early nineteen-eighties in Kentucky. Recent surveys in Europe have shown that the majority of EHV-1 isolates still belong to the 1P variant [74,93]. The impact of strain variation on vaccine performance has never been clearly established.…”
Section: Equine Herpesmentioning
confidence: 99%
“…In these organ systems, viral replication can result in vasculitis and perivasculitis ultimately resulting in abortion and reactive myeloencephalopathy, a highly lethal condition of enormous animal welfare and economic importance (7). A related alphaherpesvirus in horses, EHV-4, is predominantly associated with respiratory disease (8,9). Both viruses encode gG, a type I integral membrane protein.…”
mentioning
confidence: 99%